Assessing the effects of fjord geometry on Greenland tidewater glacier stability - Elizabeth Fischer; Andy Aschwanden (Journal of Glaciology)
Tidewater glaciers frequently advance and retreat in ways uncoupled from climate forcing. This complicates the task of forecasting the evolution of individual glaciers and the overall Greenland ice sheet, much of which is drained by tidewater glaciers. Past observational research has identified a set of processes collectively known as the tidewater glacier cycle (TGC) to describe tidewater glacier evolution in four stages: the advancing stage, the extended stage, the retreating stage and the retreated stage. Once glacier retreat is initiated, the TGC is thought to depend largely on the glacier's calving rate, which is controlled by fjord geometry. However, there has been little modeling or systematic observational work on the topic. Measuring calving rates directly is challenging and thus we developed an averaged von Mises stress state at the glacier terminus as a calving rate proxy that can be estimated from surface velocities, ice thickness, a terminus position and subglacial topography. We then analyzed 44 tidewater glaciers in Greenland and assessed the current state in the TGC for them. Of the 44 glaciers, we find that fjord geometry is causing instability in ten cases, vs stability in seven, with 11 in rapid retreat and 16 have been historically stable.